Challenges in Building Effective Deposit Insurance Systems in Developing Countries - Nolte, Jan Philipp; Rawlins, Marlon (World Bank, Washington, DC, 2017)
The FIRST Lessons Learned Series is a collection of FIRST's technical and functional insights gained from FIRST funded engagements. This knowledge note shares valuable lessons from FIRST-funded DIS projects led by the Finance and Markets Global Practice at the World Bank. The paper addresses some of the most important lessons learned and some of the key challenges faced in building effective deposit insurance systems (DIS) in developing countries.